Analisis Pengaruh Kualitas Pelayanan, Persepsi Harga dan Kualitas Produk Terhadap Keputusan Pembelian Mobil Avanza di PT. Dunia Barusa - Fitri, Fitri; Yusnaidi, Yusnaidi (Jurnal Etnik: Ekonomi-Teknik, 2023)
Service quality is an act or service within a company to meet the requirements and all needs are made to meet consumer needs. Perceived price is a consumer's assessment of the price offered whether it is appropriate and reasonable when compared to the quality of the product. Product quality is the capability, advantages, durability and functions possessed by the product. The purpose of this study was conducted to determine service quality, perceived price and product quality on purchasing decisions for Toyota Avanza cars at PTDunia Barusa. The population of Toyota Avanza car buyers and their samples is 120 buyers taken by means of the sampling method. Multiple linear regression is the analytical method used. According to research, consumer decisions to buy goods are influenced by service quality, price perceptions, and product quality